Effects of Two Herbicides on Strawberry Plants - Miroslava Soukupová; Martin Koudela (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis)
Herbicide substances aminopyralid and pyroxsulam are used to control broadleaf weeds in cereals. Disadvantage of this herbicides is fact, that their residues remain not only in the soil, but are also translocated to the plant tissues of the treated crops. Herbicide residues released from straw used like mulch by the way of decomposition and leaching can damage strawberry. In this study the response of strawberry plants to aminopyralid at doses of 3.75, 7.5 and 15 g/ha and pyroxsulam at dose 3, 15 and 30 g/ha was evaluated. With the increased concentration of both herbicides, plants injury also increased. A reduction in fruit yield was noted with both herbicides and cultivar 'Elsanta' was more sensitive than cultivar 'Karmen'. Mustang Forte herbicide at the highest rate reduced the yield of the 'Elsanta' cultivar by 52% and the 'Karmen' cultivar by 47% in the first year. However, in the second year, the decrease in yields of both varieties leveled off at 30% compared to the control. Similarly, in the case of pyroxsulam, the yield of cultivar 'Elsanta' decreased by 70% in the first year, while yield of cultivar 'Karmen' only decreased by 55%, but here the difference between cultivars remained until the second year.